Spin-valve effects in point contacts to exchange biased Сo₄₀Fe₄₀B₂₀ films - Balkashin, O.P.; Fisun, V.V.; Triputen, L.Yu.; Andersson, S.; Korenivsk, V.; Naidyuk, Yu.G. (Физика низких температур, 2014)
Nonlinear current-voltage characteristics and magnetoresistance of point contacts between a normal metal (N) and films of amorphous ferromagnet (F) Сo₄₀Fe₄₀B₂₀ of different thickness, exchange-biased by antiferromagnetic Mn8₀Ir₂₀ are studied. A surface spin valve effect in the conductance of such F–N contacts is observed. The effect of exchange bias is found to be inversely proportional to the Сo₄₀Fe₄₀B₂₀ film thickness. This behavior as well as other magneto-transport effects we observe on single exchange-pinned ferromagnetic films are similar in nature to those found in conventional three-layer spin-valves.